Natural Risks and Economic Vulnerability - IVANOVA, Valentina; ATYUKOV, Igor; VINOGRADOVA, Nadezhda; SHATIN, Andrey; IVANOV, Sergei (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019DO - 10.14505//jemt.v10.7(39).06, 2020)
Nature is not only a source of necessary conditions and resources for economic development, but also a source of dangers for the sustainability of the system of social reproduction. A characteristic feature of post-war development in almost all countries of the world is a significant increase in economic damage from natural hazards and disasters, further aggravated by the effects of climate change over the past two or three decades. This reinforces the concern of the world community, including Russia, about the problem of the dependence of the economy and society as a whole on natural assets. At the same time, the growing role of human economic activity in the genesis of natural hazards (for example, erosion, landslides, etc.), which are increasingly of a natural-anthropogenic nature (natural-man-made), attracts attention. Moreover, according to the majority of climate scientists, this role can be called decisive in enhancing climate change in recent decades. If there are certain disagreements about the last thesis, then the priority of socio-economic factors in increasing the vulnerability of economic complexes and the population to climate change and natural hazards is beyond doubt.